Assessing the influence of fly ash and polypropylene fiber on fresh, mechanical and durability properties of concrete - Abu Sayed Mohammad Akid; Saif Hossain; Md. Imtiaz Uddin Munshi; Md Manjur A Elahi; Md. Habibur Rahman Sobuz; Vivian W.Y. Tam; Md. Saiful Islam (Journal of King Saud University: Engineering Sciences, 2023)
This paper focuses on the investigation of fresh, mechanical, and durability properties of concrete with the influence of fly ash and polypropylene fiber. In this study, cement was partially replaced by 15 % and 30 % fly ash content in weight, whereas polypropylene fiber was incorporated in concrete mixes at 0.06 %, 0.12 %, and 0.18 % by volume. Twelve concrete mix proportions were developed, and slump, density, ball penetration, and compacting factor tests were conducted to examine the fresh concrete properties. Besides, mechanical characteristics, including the uniaxial compressive and splitting tensile strength of concrete, were evaluated at 7, 28, and 90 days. Further tests of concrete durability, including rapid chloride permeability test, sorptivity, and water penetration, were performed at 90 days. The results exhibited that the incorporation of fly ash developed fresh concrete properties, while polypropylene fiber decreased the fresh characteristics of concrete. Furthermore, the combination of fly ash and polypropylene fiber in concrete was substantially attained to improve the mechanical and durability characteristics compared to the control mix. Mix proportion of 15 % fly ash and 0.12 % polypropylene fiber exhibited a pronounced influence on compressive strength, chloride permeability, sorptivity, and water penetration compared to other concrete mixtures.